CORPORATE GOVERNANCE MODERATES THE EFFECT OF EFFICIENCY, INTELLECTUAL CAPITAL, LIQUIDITY ON BANKING EARNINGS MANAGEMENT - Gumala Sari, Egi; Murtanto (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to see the effect of efficiency, intellectual capital, liquidity risk on earnings management with corporate governance as a moderating variable. This research also makes This study uses purposive sampling method as a sample selection method. The population of this research is all banking companies, amounting to 45 companies. Based on predetermined criteria, a sample of 33 companies was selected with an observation period of 6 years from 2015-2020. This study found that efficiency, intellectual capital, and corporate governance have a negative effect on earnings management. The variables of liquidity risk, firm size and capital adequacy have a positive effect on earnings management. For the moderating variable, corporate governance strengthens the relationship between efficiency and earnings management, as well as intellectual capital on earnings management. The moderating variable of corporate governance weakens the relationship between liquidity risk and earnings management